Городища нижньої течії р. Сули - Вітрик, І.С. (Археологія, 1991)
У публікації розглянуто п’ять давньоруських городищ і одне пізньосередньовічне укріплення, розташовані на правому березі нижньої течії р. Сули. Экспедицией ИА АН УССР в 1979, 1985—1987 гг. изучалась оборонительная линия, расположенная на правом берегу р. Суды — от ее устья до г. Лубны,— в составе которой находились, по литературным данным, 13 древнерусских городищ. В ходе работ были уточнены планы 6 укрепленных пунктов и собраны археологические материалы конца X—XIII вв. Установлено, что в черте линии расположено II древнерусских городищ (одно укрепление в Великой Буромке оказалось позднесредневековым, а два других в этом же селе — детинец и окольный град одного городища), возникновение которых, как населенных пунктов, относится к концу X — началу XI вв. Expeditions of the Institute of Archaeology of the Ukr. SSR Academy of Sciences (1979, 1985-1987) studied the defense line on the Sula right bank (from its mouth to the town of Lubny). That line, according to data from literature, included 13 Old Rus sites of ancient towns. Plans of 6 fortified settlements were specified and archaeological materials belonging to the end of the 10-13th cent, were collected in the course of those works. It has been established that there are 11 Old Rus sites on this line (one fortification in Velikaya Buromka proved to be Late Medieval and two other ones in the same village — detinets and site outskirts) appeared a a settlements in the late 10th- early 11th centuries.